2016
DOI: 10.3892/mmr.2016.4973
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus replication is upregulated in proliferated peripheral blood lymphocytes

Abstract: Increasing evidence indicates that the hepatitis B virus (HBV) replicates in peripheral blood mononuclear cells (PBMCs), but at a low level. The present study aimed to establish a reliable and sensitive method that effectively detects HBV viral products for monitoring antiviral therapy, organ transplantation screening, and diagnosing occult HBV infection. In the present study, PBMCs (obtained from six healthy volunteers) were inoculated with HBV, and cultured with phytohemagglutinin (PHA) and interleukin‑2 (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…In the last 20 years numerous studies on the impact of HBV co-infection in the natural course of HIV infection have been carried out [57][58][59]. The finding that HBV although primarily hepatotropic also displays tropism for lymphoid cells, increased the likelihood of interaction of HIV and HBV at the cellular level, in patients with HIV/HBV coinfection [60,61]. In addition to the CD4+ T cell subpopulation, HBV also replicates in PBMC subsets of HBV/HIV-1 patients [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 20 years numerous studies on the impact of HBV co-infection in the natural course of HIV infection have been carried out [57][58][59]. The finding that HBV although primarily hepatotropic also displays tropism for lymphoid cells, increased the likelihood of interaction of HIV and HBV at the cellular level, in patients with HIV/HBV coinfection [60,61]. In addition to the CD4+ T cell subpopulation, HBV also replicates in PBMC subsets of HBV/HIV-1 patients [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Lee et al, Chemin et al, and Trippler et al have independently demonstrated that the virus is universally present in multiple immune cell subsets derived from HBV-infected individuals [ 122 , 123 , 124 ]. Studies by Yan et al and Huang et al reported that naïve primary PBMCs and hematopoietic stem cells, respectively, can be infected in vitro with clinically derived HBV [ 125 , 126 ]. Our recent work demonstrated that HBV derived from the lymphoid reservoir (PBMCs) can be stimulated with mitogens that induce an increase in multiple viral replication markers such as HBV DNA, cccDNA, and RNA both intracellularly and extracellularly [ 127 ].…”
Section: Unique Features Of Hbv That Impact Treatment and Oncogenementioning
confidence: 99%
“…PBLs were isolated from 1ml of fresh EDTA-anticoagulant peripheral venous blood with lymphocyte separation medium (LSM, Ficoll-hypaque, density at 20°C: 1.077-1.080g/ml; MP Biomedicals, USA) and washed twice with 1× phosphate buffer saline (PBS). The PBLs were then adjusted to a density of 3-5 ×10 5 cells/ml by diluting with the above complete medium in the presence of 5μg/ml of PHA (Sigma, USA) and 10 ng/ml of recombinant IL-2 (Peprotech, USA) [ 54 , 62 , 63 ]. For subcultures, the high-density cultures of PBLs were diluted with the above stimulative medium down to an appropriate seeding density every 2-3 days.…”
Section: Methodsmentioning
confidence: 99%